Functional social support and physical activity in community-dwelling older adults: a systematic review and meta-analysis - Paula Steinhoff; Lea Ellwardt; Amelie Reiner (BMC Public Health, 2026)
Abstract Background Physical activity (PA) is a key determinant of healthy ageing, yet a significant proportion of older adults remain insufficiently active. Functional social support (SOSU) – including emotional, instrumental, informational, companionship, and validation support – may facilitate PA engagement, but the strength and consistency of this association remain unclear. Methods This study conducted a systematic review and meta-analysis to examine the relationship between functional SOSU and PA in community-dwelling older adults. The electronic databases APA PsycINFO, ProQuest, PSYINDEX, PubMed, Scopus, SocINDEX, and Web of Science were searched from date of database inception until 31 March 2026. A total of 54 peer-reviewed quantitative studies, representing a total of 252,206 participants, were included in the systematic review. 91% ( n = 49) were cross-sectional and five were longitudinal studies. Thirty-three studies (55 models) contributed to the meta-analysis. Studies were assessed using the Newcastle–Ottawa Scale, and PRISMA guidelines were followed throughout. Forty-six studies were rated as good quality, seven as fair, and one as poor. Meta-analyses focused on general SOSU and social support specifically for PA (SSPA), using subjective PA outcomes. Results Findings from the systematic review suggest a mostly positive association between functional SOSU and PA, particularly for companionship and emotional support. Meta-analysis revealed a moderate significant association between general SOSU and PA (β = 0.35, 95% CI: 0.16–0.53) and a small but significant association between SSPA and PA (β = 0.12, 95% CI: 0.06–0.17). Associations were strongest for light and leisure-time PA, and more consistent in women. Longitudinal studies, though limited, suggested a positive association between SOSU and PA that appeared to remain relatively stable over time. Conclusion Functional SOSU appears to support PA in older adults, with general SOSU showing a stronger effect than SSPA. Future research should employ consistent, age-appropriate measurement tools. Additional longitudinal research is required to enable causal conclusions. Interventions integrating social support elements may improve PA uptake and promote healthier ageing.